Análise de diversidade e expressão de retrotransposons ativos em espécies de Coffea - Dias, Elaine Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The evolutionary history of the angiosperms is characterized by its rapid and broad diversification, whose background is due to the action of numerous factors; among them, the transposable elements (TEs) have been considered as one of the most important agents. TEs might compose large portions of the plant genomes, and play an important role in promoting genetic diversity. The aim of this study was to investigate the evolutionary dynamics of active TEs in the Coffea species. In the first chapter, are presented the results of an extensive analysis of the distribution and evolution in plant genomes of a retrotransposon with LTR (LTR-RT), the Copia25. Copia25 is widely distributed in the Rubiaceae family, and is present in distantly related species belonging to the Rosidae and Asteridae subclasses, and the class of monocotyledons. In particular, it was observed an incongruity involving Copia25 sequences of Musa species, a monocot, and Ixora species, a dicot (Rubiaceae), which could be due to horizontal transfer (HT) between these species or their ancestral lineages. Copia25 has a complex evolutionary dynamics in angiosperms, whose history could include conservation sequences, stochastic loss and HT. Ten LTR-RTs were annotated in C. canephora genome and had their insertional profiles obtained, using IRAP and REMAP methods, in genotypes of the parental species, C. canephora and C. eugenioides, and the allotetraploid, C. arabica. Losses of insertions could have occurred in the allotetraploid, these being more significant in five out of ten families studied, and also was observed the occurrence of directional changes in progenitors subgenomes, being more frequent those occurred in maternal subgenome, C. eugenioides. This study contributes to the understanding of the evolution of LTR-RTs within genomes, the colonization of new genomes for these elements as well as its evolutionary dynamics in a newly originated genome

A história evolutiva das angiospermas é marcada por rápida e ampla diversificação, cujo background deve-se à ação de numerosos fatores; dentre esses, os elementos de transposição (TEs) têm sido considerados como um dos agentes mais importantes. TEs podem compor grandes porções do genoma de plantas e, dessa forma, desempenhar um papel importante na promoção da diversidade genética. O objetivo deste estudo foi investigar a dinâmica evolutiva de TEs ativos em espécies do gênero Coffea. Uma ampla análise da distribuição e evolução de um retrotransposon com LTR (LTR-RT), o elemento Copia25, foi realizada em genomas de plantas. Copia25 é amplamente distribuído na família Rubiaceae, e, está presente em espécies distantemente relacionadas pertencentes às subclasses Asteridae e Rosidae, e à classe das monocotiledôneas. Em particular, foi observada uma incongruência envolvendo sequências Copia25 de espécies do gênero Musa, uma monocotiledônea, e do gênero Ixora, uma dicotiledônea (Rubiaceae), que seria devido a um evento de transferência horizontal (HT) entre essas espécies ou entre suas linhagens ancestrais. Copia25 apresenta dinâmica evolutiva complexa em angiospermas, cuja história incluiria conservação de sequências, perdas estocásticas e HT. Dez LTR-RTs foram anotados no genoma de C. canephora e tiveram seus perfis insercionais obtidos, usando os métodos de IRAP e REMAP, em genótipos das espécies progenitoras, C. canephora e C. eugenioides, e do alotetraploide, C. arabica. Perdas de inserções teriam ocorrido no alotetraploide, sendo essas mais significativas em cinco das dez famílias investigadas, e observou-se, ainda, a ocorrência de alterações direcionais nos subgenomas, sendo mais frequentes as ocorridas no subgenoma maternal, C. eugenioides. O presente trabalho contribui para o entendimento da evolução dos LTR-RTs nos genomas, da colonização de novos genomas por esses elementos,...
Keywords: Genetica molecular; Genoma; Café - Genetica; Plantas - Evolução; Molecular genetics